EFFECTS AND MECHANISMS OF DRY NEEDLING AT GV-1 ACUPUNCTURE ON VITAMIN DIGESTION AND ABSORPTION IN DIARRHEAL RABBITS - Wei Liu; Xiao Wang; Mingchao Liu a; Zhaoqing Han; Shahid Ali Rajput; Mikhlid H. Almutairi; Bader O. Almutairi; Aituan Ma; Dengshan Shiau (Journal of Animal and Plant Sciences, 2025)
Acupuncture has emerged as a novel therapeutic approach for diarrheal conditions, gaining increasing attention and utilization in recent studies due to its potential effectiveness. Notably, the GV-1 acupoint is frequently targeted for its efficacy in treating diarrheal conditions. The present study employed proteomics sequencing to disclose the possible mechanisms of rabbit diarrhea induced by Folium Sennae (FSAE) and dry needling (DN). A total of 18 rabbits were randomly allocated into three groups (n = 6), healthy control (HC), diarrhea control (DC), and GV-1. The results showed significant alterations in the rabbit colon following FSAE exposure, with 323 proteins showing notable alterations compared to the healthy controls (HC). Dry needling (DN) at GV-1 elicited alterations in the expression of 81 proteins compared with the diarrhea controls (DC). FSAE significantly changed four proteins in the vitamin digestion and absorption signaling pathway, and three of those proteins were altered by DN. Five retinol metabolism signaling pathway proteins changed considerably, caused by FSAE, and DN reversed the expression trends of three proteins. In addition, compared with the HC group, the VB7, VB12, CES2, MTHFR, Hcy, VA, Retinol, Retinal, and RA levels were significantly down-regulated. At the same time, TNF-α, IL-1β, IL-2, INF-γ, RBP4, STRA6, ADH, and RDH were markedly up-regulated in the rabbit colon of the DC group. Also, VB7, VB12, CES2, MTHFR, Hcy, VA, Ret, Retinal, and RA levels were meaningfully increased. Simultaneously, TNF-α, IL-1β, IL-2, INF-γ, RBP4, STRA6, ADH, and RDH were down-regulated in the rabbit colon of the GV-1 group. Applying GV-1 acupoint combined with DN mitigated FSAE-induced diarrhea index by modulating the expression levels of genes and proteins involved in the vitamin digestion/ absorption signaling pathway and the retinol metabolism signaling pathway. The present study demonstrated that vitamin digestion, absorption, and retinol metabolism signaling pathways are involved in the underlying mechanism of acupuncture in alleviating diarrhea. This investigation may offer novel insights into the therapeutic management of diarrhea in animals.
Keywords: Proteomics; Acupuncture; GV-1; Folium Sennae; Rabbit